Usability evaluation for geographic information systems: a systematic literature review. Issue 4 (3rd April 2019) - Unrau, René; Kray, Christian
ABSTRACT: The growing dissemination of geographic information systems (GIS) in recent years has increased the availability and use of geospatial tools. Despite this trend in GIS, usability is often not considered, and studies on usability are relatively rare. However, it has been shown that the effectiveness, efficiency and user satisfaction of these tools when used for geospatial tasks may be impacted by their design and terminology. In this article, we present a comprehensive review of the relevant literature. We analyze and compare publications of GIS usability evaluations, the methods that were used, and the findings reported. We thus produce a more detailed picture of GIS usability evaluations. Our contributions are (1) an overview of methods applied in case studies for evaluating the usability of GIS; (2) the identification of gaps and resulting weaknesses of previous studies; and (3) challenges and opportunities for future GIS usability studies. Our findings reveal a lack of usability guidelines for GIS, a lack of methods for analyzing complex workflows, and a lack of usage studies over longer periods of time. These contributions can help GIS developers and designers to improve the usability of their systems.